Pengetahuan, Pendidikan, Dukunga Hubungan Pengetahuan, Pendidikan, Dukungan Keluarga, Ibu Bekerja Dengan Pemberian ASI Perah Pada Anak Usia 0-2 Tahun - Ria Setia Sari; Ani Rifathul Rifathul Rizqi (Citra Delima Scientific journal of Citra Internasional Institute, 2021)
Background: Breast milk is breast milk that is taken by milking or milking from the mother’s breast. The importance of working mother’s knowledge about breastfeeding can be reduced by the presence of the Dairy Milking method. Research Objectives to find out knowledge, education, family support, working mothers with breastfeeding. The research method uses descriptive correlation with cross sectioanal approach. The population is 162 and the sample is 60. The data collection uses a questionnaire. Data analysis uses chi-square. The results showed that there was a significant relationship between knowledge, education, and working mothers by giving breast milk with a p-value <0,05 while for family support with giving breast milk there was no relationship because the P-value >0,05. Conclusions and Recommendations: The results of the study there is a relationship of knowledge, education, working mothers by giving breast milk, while the relationship of family support with breastfeeding does not have a relationship in children aged 0-2 years in the working area of Gembor Health Center Tangerang City in 2019.